Thermodynamic and Interfacial Properties of DTABr/CTABr Mixed Surfactant Systems in Ethanolamine/Water Mixtures: A Conductometry Study. (17th December 2013) - Esan, Olaseni Segun; Osundiya, Medinat Olubunmi; Aboluwoye, Christopher Olumuyiwa; Olanrewaju, Owoyomi; Ige, Jide
Abstract : Mixed-micelle formation in the binary mixtures of dodecyltrimethylammonium bromide (DTABr) and cetyltrimethylammonium bromide (CTABr) surfactants in water-ethanolamine mixed solvent systems has been studied by conductometric method in the temperature range of 298.1 to 313.1 K at 5 K intervals. It was observed that the presence of ethanolamine forced the formation of mixed micelle to lower total surfactant concentration than in water only. The synergistic interaction was quantitatively investigated using the theoretical models of Clint and Rubingh. The interaction parameter β 12 was negative at all the mole fractions of DTABr in the surfactant mixtures indicating a strong synergistic interaction, with the presence of ethanolamine in the solvent system resulting in a more enhanced synergism in micelle formation than in water only. The free energy of micellizationΔ G M values was more negative in water-ethanolamine mixed solvent system than in pure water indicating more spontaneity in mixed micelle formation in the presence of ethanolamine than in pure water.